Transcriptome Alterations of an in vitro-Selected, Moderately Resistant, Two-Row Malting Barley in Response to 3ADON, 15ADON, and NIV Chemotypes of Fusarium graminearum - Tucker, James R.; Legge, William G.; Maiti, Sujit; Hiebert, Colin W.; Simsek, Senay; Yao, Zhen; Xu, Wayne; Badea, Ana; Fernando, W. G. Dilantha (Frontiers in Plant Science, 2021)
Fusarium head blight caused by Fusarium graminearum is a devastating disease of malting barley. Mycotoxins associated with contaminated grain can be transferred from malt to beer and pose a health risk to consumers. In western Canada, F. graminearum has undergone an adaptive shift from 15ADON constituency to dominance by virulent 3ADON-producers; likewise, NIV-producers have established in regions of southern United States. Lack of adapted resistance sources with adequate malting quality has promoted the use of alternative breeding methodologies, such as in vitro selection. We studied the low-deoxynivalenol characteristic of in vitro selected, two-row malting barley variety “Norman” by RNAseq in contrast to its parental line “CDC Kendall,” when infected by 15ADON-, 3ADON-, and NIV-producing isolates of F. graminearum. The current study documents higher mycotoxin accumulation by 3ADON isolates, thereby representing increased threat to barley production. At 72–96-h post infection, significant alterations in transcription patterns were observed in both varieties with pronounced upregulation of the phenylpropanoid pathway and detoxification gene categories (UGT, GST, CyP450, and ABC), particularly in 3ADON treatment. Defense response was multitiered, where differential expression in “Norman” associated with antimicrobial peptides (thionin 2.1, defensing, non-specific lipid-transfer protein) and stress-related proteins, such as late embryogenesis abundant proteins, heat-shock, desiccation related, and a peroxidase (HvPrx5). Several gene targets identified in “Norman” would be useful for application of breeding varieties with reduced deoxynivalenol content.